MENJADI GURU YANG BERDAMPAK: STRATEGI MENINGKATKAN KINERJA DI KELAS - Wahyuni Siti Masiroh; Fitri Widiastuti; Puspa Leli Rahmadania; Muhammad Ali Murtadho; Siti Zazak Soraya (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
This study aims to analyze the role and influence of teachers in impacting learning, as well as to examine strategies for improving teacher performance through the role of the principal. The study employed a literature review method utilizing national and international journal sources indexed in Google Scholar, Garuda, DOAJ, Scopus, and other academic databases for the period 2020–2026. The data analysis technique used was content analysis, which involves identifying, categorizing, interpreting, and evaluating the content of various relevant literature to discover patterns, concepts, and interrelationships between ideas, resulting in a systematic, objective, and in-depth synthesis of the study. The results of the study indicate that impactful teachers not only act as conveyors of material but also as facilitators, motivators, and role models in shaping student character. Teachers who are able to create active learning, adapt strategies to needs, and build good relationships with students have been shown to improve student motivation and learning outcomes. In addition, strategies for improving teacher performance can be implemented through continuous coaching, supervision, motivation, and performance evaluation by the principal to improve the quality of learning in schools.